2011
DOI: 10.1016/j.ygeno.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Acute involution in the tammar wallaby: Identification of genes and putative novel milk proteins implicated in mammary gland function

Abstract: Marsupials provide a suitable alternative model to studying mammary gland involution. They have evolved a different reproductive strategy from eutherians, giving birth to an altricial young and secreting milk that changes in composition during lactation. In this study, we used a marsupial-specific EST microarray to identify 47 up-regulated genes during mammary gland involution in the tammar wallaby (Macropus eugenii). These include the pro-apoptotic tumour necrosis factor receptor superfamily 21 (TNFRSF21) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…It has been observed that LALBA expression is strongly induced by the onset of lactation in several species (27), decreases in late lactation in bovine (27), and further decreases at the onset of involution as observed in bovine and kangaroo (111,171). The expression of LALBA increases upon treatment with a cocktail of lactogenic hormones (i.e., insulin ϩ hydrocortisone ϩ prolactin ϩ 17␤-estradiol or growth hormone), as observed in mouse and bovine mammary cells in vitro (105,199).…”
Section: Transcriptional Regulation Of the Lactose Synthase Enzymes Lmentioning
confidence: 87%
“…It has been observed that LALBA expression is strongly induced by the onset of lactation in several species (27), decreases in late lactation in bovine (27), and further decreases at the onset of involution as observed in bovine and kangaroo (111,171). The expression of LALBA increases upon treatment with a cocktail of lactogenic hormones (i.e., insulin ϩ hydrocortisone ϩ prolactin ϩ 17␤-estradiol or growth hormone), as observed in mouse and bovine mammary cells in vitro (105,199).…”
Section: Transcriptional Regulation Of the Lactose Synthase Enzymes Lmentioning
confidence: 87%
“…ELP gene expression in the tammar mammary gland was investigated by analysing a microarray database [69,102-104] produced from custom-made cDNA microarray slides and total RNA collected from glands at each phase of the lactation cycle [69,102-104]. Glass microarray slides were printed by the Peter MacCallum Cancer Centre Microarray Core Facility, Melbourne, Australia and contained 10,368 tammar cDNA spots which were derived from a commercially prepared (Life Technologies, Rockville, MD, USA), normalised 15,001 tammar mammary gland EST (expressed sequence tag) library.…”
Section: Methodsmentioning
confidence: 99%
“…These included: day 26P, d55L, d87L, d130L, d180L, d220L, d260L and d5I (tissue from a d45L female 5 days after removal of the pouch young (RPY)) [19]. Gene expression changes in the tammar mammary gland during the reproductive cycle were investigated by a large-scale microarray experiment involving 36 comparisons (72 slides including dye swaps, 144 channels in total) [69,102-104]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the use of a marsupial-specific microarray to investigate differential gene expression has identified 47 genes upregulated during mammary gland involution. Among these are genes that could potentially play a protective role against mammary gland infection, such as ABP1, C1QB, C4A, and CSF2R β [97]. …”
Section: Lactation Genesmentioning
confidence: 99%